2002
DOI: 10.1203/00006450-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Natural Reinfection with Respiratory Syncytial Virus Does Not Boost Virus-Specific T-Cell Immunity

Abstract: To determine the role of respiratory syncytial virus (RSV)-specific cell-mediated immunity during natural reinfection, we investigated whether RSV-specific T-cell responses protect against reinfection and, subsequently, whether reinfection boosts virusspecific memory. In a cohort of 55 infants who were hospitalized for RSV bronchiolitis, RSV-specific lymphoproliferative responses in the peripheral blood were measured at three time-points: on admission, 4 wk after admission, and 1 y later, after the second wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…Reinfection with RSV can occur throughout life, indicating that RSV antibody responses only partially provide protection and only for a limited period of time (2,53). Prophylactic palivizumab is able to prevent severe RSV-induced respiratory tract disease in most, but not all, patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reinfection with RSV can occur throughout life, indicating that RSV antibody responses only partially provide protection and only for a limited period of time (2,53). Prophylactic palivizumab is able to prevent severe RSV-induced respiratory tract disease in most, but not all, patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to reflect strong immune pressure and the subsequent 66 generation of escape variants, in a process analogous to antigenic drift in the hemagglutinin (HA) 67 protein in influenza A virus [12,13]. Hence, reinfection with RSV is commonplace [14,15] …”
mentioning
confidence: 99%
“…It has been shown that evaluating effector/memory function in systemic compartments such as peripheral blood may not provide an adequate assessment of the local response to RSV [29, 30]. Although the studies reported here were carried out in adult human peripheral blood and not in the human lung and numbers of donors are limited, we suggest that the production of Th1- or Th2-type cytokines in response to RSV is controlled differentially by the nature of the RSV antigenic stimulus and host immune status.…”
Section: Discussionmentioning
confidence: 99%